Effects of mid-thermal and ultraviolet treatments on Listeria innocua inactivation in pineapple juice. - Sew, Chang Chew; Mohd Ghazali, Hasanah; Olga, Martin-Belloso; Mohd Adzahan, Noranizan (2012)
Ultraviolet (UV) treatment has been proven effective for killing a variety of microorganisms in liquid foods and on the surfaces of solid foods. However, there is a growing concern of inadequate decontamination in coloured and turbid fluids containing UV-absorbing compounds. Thus, the main objective of this work was to examine the microbiocidal effect of mid-thermal and UV treatments on L. innocuo reduction in pineapple juice. Pineapples were peeled and cubed prior to juice extraction. The extracted juice was clarified using pectinase Ultra SP-l and filtered before inoculation with surrogate L. Innoeuo. The inoculated juice was given 4 separate treatments: (i) mid-thermal heating at 55 ·C for 10 minutes, (iI) UV treatments at different dosages (1.7 - 11.1 mJ/cm'), (iii) mid-thermal heating followed by UV treatments at different dosage, and (iv) heat pasteurisation at 95 ·C for 1 minute. The control sample was untreated pineapple juice. Exposure to mid-thermal heating caused a 4.62 ±0.40 log reduction of L. Innocuo, while the highest decontamination level achieved within the various UV doses applied (without mid-thermal treatment) was 2.16 ± 0.10 log reduction at 11.06 mJ/cm'. Results showed that the mid-thermal treatment increased the absorption coefficient of pineapple juice from 16.7 cm-' to 27.8 cm-', which increases the lethality of UV treatment. When mid-thermal treated juices were further treated with UV, an inactivation of N7 log reduction was observed indicating a synergistic effect. Similar level of inactivation was observed for conventionally pasteurised juices. Thus, the combined treatments could be a possible solution for pasteurising juices in cases when UV treatment alone is not sufficient.